Generations Y and Z and their perceptions of occupational safety and health (Research, Society and Development, 2020)
The concept of generation encompasses the set of individuals born at different times, influenced by a historical context, which determines behavior, causing a direct impact on the evolution of society and, mainly, on the work environment. This study aimed to analyze the behaviors of Generations Y and Z, pointing out the causes and differences in the way of thinking and proceeding regarding the perception of risk factors for safety and health at work. We sought to understand the main meanings referenced to work by the individuals of these two generations, what their ways of thinking and acting on a daily basis in society, the view that other generations conceive of them and, still, some similarities and differences between generations surveyed. To this end, a qualitative research was carried out, in which data were collected through a questionnaire answered by individuals belonging to Generations Y and Z operating in the market. After analysis, it was found that the characteristics pointed out for Generations Y and Z occur in line with what is prescribed in the researched literature. Actions were proposed to improve the perception of occupational health and safety risks for the generations under study.